Study Pore Characterization of γ-Alumina – Activated Carbon Composite Made of Cassava Peels (Manihot esculenta Cranz) - Hartini Hartini; Yuniawan Hidayat; Mudjijono Mudjijono (ALCHEMY Jurnal Penelitian Kimia, 2015)
A composite of γ-alumina and activated carbon made of cassava peels was studied in terms of its pore structures and its properties. The objective of this study was to determine the interaction and structure, as well as the character and pore size of γ-alumina – activated carbon composite.Carbon made of cassava peels was activated by H2SO4 and its activities were tested according to the Indonesian Industrial Standards (SII). The addition of activated carbon into γ-alumina made in variations of 10, 20, 30, 40 and 50 % w/w, of the total weight of 10 grams. The composite of γ-alumina - activated carbon was characterized by FTIR, SAA (Surface Area Analyzer), XRD, and determination of Hysteresis Loop composites.The greater addition of activated carbon to γ-alumina causes intermolecular interactions between –O-H groups form rehydrated hydrogen bonds in the composite is greater. The structure of γ-alumina in the composites remain intact although the percentage of activated carbon in composite is large. The total pore volume and surface area using the BET method of the composite decreases with increasing activated carbon percentage. The greater addition of activated carbon to γ-alumina causes size of mesoporous composites decreased with the characteristic of a composite formed is closer to the activated carbon.